Paediatric Strategy Forum for medicinal product development of multi-targeted kinase inhibitors in bone sarcomas: ACCELERATE in collaboration with the European Medicines Agency with participation of the Food and Drug Administration. (September 2022) - Pearson, Andrew DJ.; Gaspar, Nathalie; Janeway, Katherine; Campbell-Hewson, Quentin; Lawlor, Elizabeth R.; Copland, Chris; Karres, Dominik; Norga, Koen; Benzaghou, Fawzi; Weiner, Susan; Weigel, Brenda; Weiss, Aaron R.; et al.
Abstract: The eighth Paediatric Strategy Forum focused on multi-targeted kinase inhibitors (mTKIs) in osteosarcoma and Ewing sarcoma. The development of curative, innovative products in these tumours is a high priority and addresses unmet needs in children, adolescents and adults. Despite clinical and investigational use of mTKIs, efficacy in patients with bone tumours has not been definitively demonstrated. Randomised studies, currently being planned or in progress, in front-line and relapse settings will inform the further development of this class of product. It is crucial that these are rapidly initiated to generate robust data to support international collaborative efforts. The experience to date has generally indicated that the safety profile of mTKIs as monotherapy, and in combination with chemotherapy or other targeted therapy, is consistent with that of adults and that toxicity is manageable. Increasing understanding of relevant predictive biomarkers and tumour biology is absolutely critical to further develop this class of products. Biospecimen samples for correlative studies and biomarker development should be shared, and a joint academic-industry consortium created. This would result in an integrated collection of serial tumour tissues and a systematic retrospective and prospective analyses of these samples to ensure robust assessment of biologic effect of mTKIs. To support access for children to benefit from these novel therapies, clinical trials should be designed with sufficient scientific rationale to support regulatory and payer requirements. To achieve this, early dialogue between academia, industry, regulators, and patient advocates is essential. Evaluating feasibility of combination strategies and then undertaking a randomised trial in the same protocol accelerates drug development. Where possible, clinical trials and development should include children, adolescents, and adults less than 40 years. To respond to emerging science, in approximately 12 months, a multi-stakeholder group will meet and review available data to determine future directions and priorities. Highlights: mTKIs are being evaluated in osteosarcoma and Ewing sarcoma. Ongoing or planned randomised studies will inform further development. Toxicity is tolerable when mTKIs are combined with chemotherapy. Increased understanding of predictive biomarkers and tumour biology is crucial. A joint academic-industry consortium should share and analyse biomarker samples.